Polityczne znaczenie Sudetów i Karpat - Ławniczak, Artur (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Mountains are stable and evident phenomenon, especially in contrast with large lowland, as in case of Poland. They determine separateness of the greatest West Slavonic nation from its southern neighbours. On the other hand, in the past Carpathians and Sudeten were a scarcely populated area, entered by the German from the west and Walachian from the south-east migrants, with important cultural and political consequences. The effect was the diversification of ethnical landscape, with consequences for the process of shaping of modern nations, especially in the case of Slovak nation, which absorbed the great part of eastern, shepherd imigration. For Czechs and Hungarians mountains were protection from German or Slavic environment. Slavic nations after the second World War were situated, as an effect of ethnical cleansing, in national states with large “Wild Camps” in depopulated German or Ukrainian highlands. In this situation especially valuable is the old community of Polish highlanders, perceived abroad as stereotyped Poles with great love for homeland and liberty.
Keywords: Europa Środkowo-Wschodnia; góry; geopolityka; determinizm geograficzny; penetracja narodowościowa i kulturowa; genius loci; znaczenie góralskiego stylu życia